Enactment of apology legislation in Hong Kong: Report and second round consultation - WONG, Lisa (Institutional Knowledge at Singapore Management University, 2016)
Nadja Alexander was contributor to the Report of the Department of Justice of Hong Kong as Chair of the Working Group.In the report published by the Working Group on Mediation of the Department of Justice in 2010, it was recommended, among others, that the question of whether there should be an apology or legislative provisions dealing with the making of apologies for the purpose of enhancing settlement deserves further consideration. In 2012, for Secretary for Justice established the Steering Committee on Mediation ("Steering Committee") with a view to further promoting the development of mediation in Hong Kong. The regulatory Framework Sub-Committee is a sub-committee set up under the Steering Committee and its has been tasked to consider whether there is a need to introduce apology legislation in Hong Kong.